Peran Teknologi Blockchain dalam Meningkatkan Keamanan Transaksi Keuangan - Wahyu Ramadhana (Journal of Public Sector Financial Management, 2025)
The proliferation of digital financial technology presents a major challenge in maintaining transaction security. One prominent innovation is blockchain technology, which offers decentralisation, transparency, and advanced cryptographic mechanisms. This article examines the concept of blockchain, its working mechanism, and its role in improving the security of financial transactions. The analysis is conducted through a literature study of various international journals, industry reports, and case studies in the banking, fintech, and cryptocurrency sectors. The results show that blockchain can minimise the risk of data manipulation, improve the efficiency of the verification process, and strengthen user trust.